موقف الشيخ عبدالله الفارسي من آيات الصفات في ترجمته للقرآن الكريم إلى اللغة السواحلية – دراسة وصفية نقدية: Sheikh ʿAbdullah al-Farsī’s Position on the Verses of Divine Attributes in His Swahili Translation of the Qurʾān: A Descriptive-Critical Study - Sanbur Adan, Abdiwahab; Abdulrahman, Manswab Mahsen (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث تعنى هذه الدراسة بإبراز موقف الشيخ عبدالله الفارسي من آيات الصفات في ترجمته الشهيرة لمعاني القرآن الكريم إلى اللغة السواحلية. والموضوع مع عظم شأنه وتعلقه بباب هو من أهم أبواب الدين، فإن مباحثه المعروضة في الترجمة المشار إليها آنفا لم يلق عناية الباحثين، ولم تُدرس دراسة شاملة تكشف عن موقف صاحبها منها. ولتحقيق هذا الهدف فقد سلك الباحث المنهج الوصفي التحليلي، وذلك بتتبع عبارات المؤلف المتعلقة بالصفات الإلاهية سواء كانت موضوعة في متن الترجمة أو واردت في الحاشية، وجمعها، وترجمتها إلى اللغة العربية، ثم استخلاص مدلولاته العلمية، مع إجراء دراسة نقدية على المسائل المستخلصة بعرضها على النصوص الشرعية وأقوال من سبقه من المفسرين وغيرهم، لإدراك مدى موافقتها أو مخالفتها للعقيدة الصحيحة الموروثة عن السلف الصالح. ومن أهم ما توصل إليه الباحث أن الشيخ الفارسي خالف مذهب السلف في تأويله لصفة الرحمة، والوجه، والاستواء، والإتيان والمجيئ، بينما وافقهم في إثبات صفة السمع، والبصر، والكلام، والعين، واليدين، والعلو، والرضا والغضب. ABSTRACT This study aims to highlight Sheikh Abdullah al-Farsi’s position on the verses concerning Allaah’s attributes in his renowned translation of the meanings of the Holy Quran into Swahili. Despite the subject’s importance and its connection to one of the most crucial aspects of the faith, the discussions presented in the aforementioned translation have not received sufficient scholarly attention, nor have they been studied comprehensively to reveal the author’s stance on them. To achieve this objective, the researcher adopted a descriptive-analytical approach, tracing the author’s statements related to divine attributes, whether found in the main text of the translation or in the footnotes. These statements were collected, translated into Arabic, and their scholarly implications were extracted. A critical analysis of these extracted points was then conducted, comparing them to Islamic texts and the statements of earlier commentators and others, to determine their conformity or contradiction with the sound doctrine inherited from the righteous predecessors. Among the most significant findings of the researcher is that Sheikh al-Farsi deviated from the Sunni belief in his interpretation Allaah’s attributes of Mercy, Face, Istiwa’ and Coming, while agreeing with them in affirming the attributes of Hearing, Seeing, Speech, Eye, Hands, Exaltedness, Pleasure and Anger.